Erosion Hazard Level Prediction in Catchment Area Way Rarem Dam Lampung Province - Suprapto Suprapto; Aniessa Rinny Asnaning (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
The objectives of this research are to identify and evaluate the erosion in the catchmentÂ area of Way Rarem Dam, by predicting the magnitude of erosion using the Universal Soil Loss Equation (USLE). The outcome of this activity is the maps of erosion potential Catchment Area of Way Rarem Dam , which can be used as a guide in planning further handling. The field survey was conducted to cross check the locations suspected of having land use changes quickly in order to update data that already exist in accordance with current conditions. Calculation of the amount of erosion prediction using USLE equation is A = R x K x LS x CP. Based on the results obtained map making extensive catchment (Catchment Area) Reservoir Way Rarem namely 32864.8 ha (328.648 km ), which consistsof a class of very severe erosion very weight level covering 104.461 km2 (31.78%), weight level measuring 89.998 km 2 ( 27.38%), middle level mesuring 38.856 km (11.82%), light level measuring 92.262 km2 (28.07%), and very light level measuring 3,071 km (0.95%). The average rate of erosion in the catchment reservoirs Way Rarem which amounted to 238.33 tons/ha/year, which is classified in class IV of erosion levels or weight category.Keywords: erosion hazard level, catchment area